(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2018)
Background : Among the different complications of chronic liver diseases, anemia is not uncommon. This study is done to evaluate the frequency and pattern of anemia among the patients with Chronic Liver Disease (CLD) admitted in a tertiary care hospital of Bangladesh.100 admitted patients of CLD was evaluated for prevalence and pattern of anemia. Materials and methods : Sampling was purposive non random according to inclusion criteria. After clinical evaluation 5 cc venous blood was collected and sent to the Department of Haematology for haematological profile analysis. Male to female ratio was found 3.1:1. From the age distribution of the patients, highest number (45%) was found in the age group of 30-49 years. Results : Hematological abnormality were detected in 85 (85%) of patients. The various abnormality included anaemia (76%) neutropenia (5%) lymphopenia (6%) thrombocytopenia (47%) pancytopenia(5%). Patients had anemia due to various causes including iron deficiency anemia (85.5%) and Anemia of Chronic Diseases (ACD) 11.8%. Fifty percent (50%) patients had severe anemia where Hb was 6.46± 0.9 gm%. Normocytic normochromic anemia (NNA) was found 30.26%, normocytic hypochromic anemia was found 31.57% and microcytic hypochromic anemia was found 38.15%. Conclusion : Liver diseases are frequently associated with hematological abnormalities. Anemia of diverse etiology occurs in many of these patients. JCMCTA 2017 ; 28 (2) : 111-115